A ciência, os cientistas e a dupla hélice sob o olhar de estudantes - Massarani, Luisa (2001)
Analyse aspects of scientific culture in Brazil, considering as starting point quantitative and qualitative studies undertaken among high school and undergraduate students in Rio de Janeiro. We analysed 1,065 questionnaires, 455 of them completed by students of five courses of the Federal University of Rio de Janeiro (Social Sciences, Biology, Medicine, Engineering and Physics) and 610 by students of nine high schools (370 of them 370 of them attended government schools and 240 private schools). This first section of the research aimed to investigate the attitudes that young people have towards science, scientist's work and applications and consequences of scientific research. We also analysed the point of view these students have towards new technologies and uses of modem genetics. The role of genes in the development of individual characteristics has been considered too. A focus group method was used with GATTACA, a science fiction film, the catalyst for discussion. The research doesn't seek to be a representative sample of the Brazilian students' population or even of Rio de Janeiro. It is a case study, in which we provided a descriptive study of the analysed groups and discussed the results we obtained. in our reflections we have taken in to account several conceptions concerning scientific culture which were supported by observations and analysis of the context of the mass media in which these young people were placed. Some possible implications of the results for the popularization of science activities are also discussed.